Transient underwater acoustic channel simulator development - Caley, M.; Duncan, Alec (Australian Acoustical Society, 2013)
The underwater communication channel is often characterised by transient reinforcement and fading of multiple transmission paths, such that no single transmission path can be generally relied upon to provide a continuous communication channel. For smooth to moderate seas the transient real ocean channel may be conceptualised as a timeseries of static channel 'snap-shots'. For a static channel geometry and transmission medium, ray- Tracing methods enable calculation of the channel impulse response for the relatively high frequencies associated with data communications. This leads to the modelling challenge of how a series of static channel responses may be seamlessly joined to create a transient channel response simulation that achieves realistic multi-path fading, and arrival time spreading (or synonymously Doppler frequency spreading) of an arbitrary communications signal. This paper describes algorithms that have been explored to identify emergent, continuing and extinguishing channel transmission paths from one 'snapshot' impulse response to the next. The calculation architecture being developed to simulate the transient channel response is described. Copyright © (2013) by the Australian Acoustical Society.